2017
DOI: 10.5194/acp-17-8825-2017
|View full text |Cite
|
Sign up to set email alerts
|

Observations of particles at their formation sizes in Beijing, China

Abstract: Abstract. New particle formation (NPF) has been observed in many highly polluted environments of South East Asia, including Beijing, where the extent of its contribution to intense haze events is still an open question. Estimated characteristics of NPF events, such as their starting times and formation and growth rates of particles, are more accurate when the detection range of particles extends to smaller sizes. In order to understand the very first steps of particle formation, we used a neutral cluster and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…For the other 2 events, it was 49.8 and 40.5 µg m −3 , respectively. In another campaign in Beijing during January 2016 (Jayaratne et al, 2017), 14 NPF events were observed. Among them, 12 events occurred when the daily-average PM 2.5 mass concentration was lower than 30 µg m −3 .…”
Section: Predicting Npf Days Using Pm 25 Mass Concentrationmentioning
confidence: 99%
“…For the other 2 events, it was 49.8 and 40.5 µg m −3 , respectively. In another campaign in Beijing during January 2016 (Jayaratne et al, 2017), 14 NPF events were observed. Among them, 12 events occurred when the daily-average PM 2.5 mass concentration was lower than 30 µg m −3 .…”
Section: Predicting Npf Days Using Pm 25 Mass Concentrationmentioning
confidence: 99%
“…In this study, a neutral cluster and air ion spectrometer (NAIS), which could detect particle size distribution down than 3 nm, was used. The NAIS greatly avoided the misleading interference of primary emission, and it measured more accurate particle formation sizes (Jayaratne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…found that the Fuchs surface area (which is a representative parameter of coagulation scavenging based on kinetic theory and is proportional to CS) fundamentally determined the occurrence of NPF events. The Fuchs surface 10 area had a good correlation with the PM2.5 mass concentration, and no NPF event was observed when the daily mean PM2.5 concentration was higher than 43 μg m -3 in the winter of 2015 in Beijing (Jayaratne et al, 2017). However, in some cases, the CS or the average coagulation sinks during NPF events were not significantly lower compare to other times when new particles were not formed, indicating that other factors, such as the precursor vapors and photochemical activity, might also play an important role in driving NPF (Gong et al, 2010).…”
Section: Npf Frequencymentioning
confidence: 96%
“…Many studies about NPF in China measured only particles larger than 10 nm, while a few studies also measured particles with diameters in the range of 3-10 nm. However, the information of particles smaller than 3 nm is quite limited due to the lack of detection 15 instruments, and only few studies reported measurement results of sub-3 nanoparticles (Xiao et al, 2015;Jayaratne et al, 2017). As for gas phase precursors, direct measurements of H2SO4 were carried out with atmospheric pressure-ion drift-chemical ionization mass spectrometer (AP-ID-CIMS) in a few studies (Yue et al, 2010;Zheng et al, 2011;Wang et al, 2011), while other studies usually estimated H2SO4 concentrations using different proxies related to SO2, radiation, O3, and relative humidity (RH).…”
Section: Overview Of Npf Research In Chinamentioning
confidence: 99%
See 1 more Smart Citation